2021
DOI: 10.3390/ijms222111975
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Limbal Epithelial Stem Cells: Importance of the Niche

Abstract: Limbal epithelial stem/progenitor cells (LSCs) reside in a niche that contains finely tuned balances of various signaling pathways including Wnt, Notch, BMP, Shh, YAP, and TGFβ. The activation or inhibition of these pathways is frequently dependent on the interactions of LSCs with various niche cell types and extracellular substrates. In addition to receiving molecular signals from growth factors, cytokines, and other soluble molecules, LSCs also respond to their surrounding physical structure via mechanotrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 147 publications
1
10
0
Order By: Relevance
“…Several studies in recent years have highlighted the importance of maintaining the limbal niche for the proper functioning of LESCs. 36,37 Previous studies reported an increase in lipid content in diabetic corneas, with the most significant increase in sphingosine, whose phosphorylation product affected wound healing. 38 The current study concluded that LDL and TC correlated with stem cell parameters, suggesting that lipid metabolism dysfunction within the limbal niche potentially influenced LESCs, as previously reported in other stem cell microenvironments.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in recent years have highlighted the importance of maintaining the limbal niche for the proper functioning of LESCs. 36,37 Previous studies reported an increase in lipid content in diabetic corneas, with the most significant increase in sphingosine, whose phosphorylation product affected wound healing. 38 The current study concluded that LDL and TC correlated with stem cell parameters, suggesting that lipid metabolism dysfunction within the limbal niche potentially influenced LESCs, as previously reported in other stem cell microenvironments.…”
Section: Discussionmentioning
confidence: 99%
“…The normal limbus and LSCs act as a barrier to prevent conjunctival epithelial cells from invading the cornea [ 22 ]. LSCs are quiescent stem cells that can be activated to divide symmetrically and asymmetrically, producing proliferative progenitor cells that produce mature corneal epithelial cells [ 23 ]. Our results demonstrated that the addition of exogenous MLN4924 in vivo and in vitro could effectively maintain the stemness of LSCs and promote LSC proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular regulation of LSCs is another approach to supplement soluble factors that sustain the self-renewal of LSCs both in vitro and in vivo. Several signaling pathways such as Wnt, Notch, BMP, Shh, YAP, and TGFb play critical roles in the maintenance and differentiation of LSCs [40][41][42][43][44]. Activation of Wnt signaling and modulation of Notch signaling are shown to impact the LSC proliferation and differentiation in culture, which opens a new approach in enhancing LSC expansion efficiency and survival of LSCs upon chemical injury in culture [45].…”
Section: Restoration Of Limbal Stem Cell Nichementioning
confidence: 99%